Linkage Analysis of Agricultural Sector and Effect on the Economy in Indonesia (Input-Output Analysis) - Retno Febriyastuti Widyawati (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: Linkage Analysis of Agricultural Sector and Effect on the Economy in Indonesia (Input-Output Analysis). The agricultural sector is still the mainstay of job creation in large enough quantities compared to other sectors of the economy in Indonesia. It makes the chances of the agricultural sector in its influence on the economy in Indonesia. This article aims to examine the relationship forward and backward linkages agricultural sector with other sectors in Indonesia and examines the impact of multiplier output agriculture sector on the economy. Analysis use Input-Output with secondary data Input-Output Indonesia 2010. The results showed that the manufacturing sector and electricity, gas, water sector had been linked to the future of the agricultural sector. Furthermore, electricity, gas, water sector; and the building sector have backward linkages to the agriculture sector. The multiplier output agricultural sector has multiplier output impact lower than other sectors in the economy. Multiplier household income and employment agriculture have a greater multiplier effect than other sectors. Keywords: Agriculture, Input-Output, Linkages, Multiplier EffectAbstrak: Analisis Keterkaitan Sektor Pertanian dan Pengaruhnya Terhadap Perekonomian di Indonesia (Analisis Input Output). Sektor pertanian masih menjadi andalan penciptaan lapangan pekerjaan dalam jumlah yang cukup besar dibandingkan dengan sektor-sektor lainnya dalam perekonomian di Indonesia. Hal ini menjadikan peluang sektor pertanian dalam pengaruhnya terhadap perekonomian di Indonesia. Artikel ini bertujuan untuk meneliti keterkaitan ke depan dan ke belakang sektor pertanian dengan sektor-sektor lain di Indonesia dan meneliti dampak dari angka pengganda sektor pertanian. Analisis yaitu Input-Output dengan data sekunder Input-Output Indonesia 2010. Hasil menunjukkan bahwa sektor industri pengolahan dan sektor listrik, gas, air bersih memiliki keterkaitan ke depan terhadap sektor pertanian. Selanjutnya, sektor listrik, gas, air bersih; dan sektor bangunan memiliki keterkaitan ke belakang terhadap sektor pertanian. Hasil pengganda output sektor pertanian memiliki dampak pengganda output yang lebih rendah dibandingkan sektor lainnya, sedangkan pengganda pendapatan rumah tangga dan kesempatan kerja memiliki dampak pengganda yang lebih besar dibandingkan sektor lainnya. Kata Kunci: Pertanian, Input-Output, Keterkaitan, Angka Pengganda